Kansas City Startup Village: a case study - Lewis, Amelia (Kansas State University, 2016)
Innovative communities create cities rich in culture and opportunities to attract like minded residents and business owners to advance their city and their community. This study looks at the entrepreneurial startup community, Kansas City Startup Village (KCSV) and seeks to understand how social networks benefit entrepreneurs and how KCSV helps establish these networks. Through a review of similar startup communities and literature surrounding the topic, essential components within startup communities and characteristics of entrepreneurs were identified. To better understand the role of these elements within KCSV, ten entrepreneurs and members of support organizations of KCSV were interviewed regarding the social networks of the Village. The interviewing process utilized a grounded theory approach, with a text coding and analysis of the transcribed interviews to identify the role of entrepreneurs and social networks within KCSV. Findings were consistent with many of the topics discussed in the literature review and within the Comparative Communities section. Kansas City shares many common elements of the startup communities of Saint Louis, Missouri, and Boulder, Colorado; most notably the networking and social capital-building practices that keep entrepreneurs connected. The entrepreneurs possess traits that gave them an entrepreneurial advantage including formal education, past business experience, risk taking, and broad, forward thinking goals. Strong and weak ties were used in different scenarios and at different stages within their company’s lifecycle to assist with opportunity identification, resource acquisition and gaining legitimacy. KCSV was most influential in establishing the peer networks of entrepreneurs, which assist primarily with opportunity identification and resource acquisition.
Keywords: Entrepreneurship; Urban Planning; Social Networks; Startups; Startup Communities